2018
DOI: 10.1093/ibd/izy264
|View full text |Cite
|
Sign up to set email alerts
|

The PROSIT Cohort of Infliximab Biosimilar in IBD: A Prolonged Follow-up on the Effectiveness and Safety Across Italy

Abstract: In this large prospective cohort, no further signals of difference in safety and effectiveness of CT-P13 in IBD has been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 39 publications
4
51
1
Order By: Relevance
“…The results showed non-inferiority of CT-P13 in comparison with the reference drug in the overall study population (n = 482), although the analysis of each disease sub-group is not reliable due to underpower. Such reassuring findings have been confirmed in a large prospective cohort of IBD patients treated with CT-P13: in particular, among all subjects included in this study (n = 810), 155 were switched from infliximab originator to the biosimilar, with no increase of adverse events and without affecting persistence of therapy [6]. The SECURE trial [7] analyzed as primary endpoint the serum drug level of CT-P13 16 weeks after switching from the originator in patients with IBD in clinical remission: results showed no differences in the pharmacokinetics and confirmed comparable outcomes in terms of efficacy and safety.…”
Section: Infliximab Biosimilars In Ibd: the Evidencesupporting
confidence: 66%
“…The results showed non-inferiority of CT-P13 in comparison with the reference drug in the overall study population (n = 482), although the analysis of each disease sub-group is not reliable due to underpower. Such reassuring findings have been confirmed in a large prospective cohort of IBD patients treated with CT-P13: in particular, among all subjects included in this study (n = 810), 155 were switched from infliximab originator to the biosimilar, with no increase of adverse events and without affecting persistence of therapy [6]. The SECURE trial [7] analyzed as primary endpoint the serum drug level of CT-P13 16 weeks after switching from the originator in patients with IBD in clinical remission: results showed no differences in the pharmacokinetics and confirmed comparable outcomes in terms of efficacy and safety.…”
Section: Infliximab Biosimilars In Ibd: the Evidencesupporting
confidence: 66%
“…Nevertheless, our finding is not unique: a recent study of gastroenterologists in the United States found that half of 500 interviewees considered the risk of side effects a barrier in prescribing biologics to UC patients. 27 As new biological drugs with different mechanisms of action and likely better safety profiles (eg vedolizumab and ustekinumab) become available, and as Italian physicians gain experience with biologic therapies, including biosimilars, 28 we can expect that the prescription of these drugs in Italy will become more confident and widespread.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence base in IBD has grown substantially in the intervening years. Indeed, a recent randomised phase 3 trial definitively showed the non-inferiority of a biosimilar infliximab to the originator product in IBD [38] , and this has been supported by data from multiple 'real-world' studies [39][40][41][42].…”
Section: Anti-tnf Biosimilars In Ibd Management: Growing Confidence Amentioning
confidence: 92%